Boosted protease inhibitor monotherapy versus boosted protease inhibitor plus lamivudine dual therapy as second-line maintenance treatment for HIV-1-infected patients in sub-Saharan Africa (ANRS12 286/MOBIDIP): a multicentre, randomised, parallel, open-label, superiority trial. Issue 9 (September 2017) - Ciaffi, Laura; Koulla-Shiro, Sinata; Sawadogo, Adrien Bruno; Ndour, Cheik Tidiane; Eymard-Duvernay, Sabrina; Mbouyap, Pretty Rosereine; Ayangma, Liliane; Zoungrana, Jacques; Gueye, Ndeye Fatou Ngom; Diallo, Mohamadou; Izard, Suzanne; Bado, Guillaume; et al.
Summary: Background: Despite satisfactory efficacy of WHO-recommended second-line antiretroviral treatment for patients with HIV in low-income countries, the need for simplified, low-cost, and less-toxic maintenance strategies remains high. We compared boosted protease inhibitor monotherapy with dual therapy with boosted protease inhibitor plus lamivudine in patients on second-line antiretrovial therapy (ART). Methods: We did a multicentre, randomised, parallel, open-label, superiority, trial in the HIV services of five hospitals in sub-Saharan Africa (Yaoundé, Cameroon; Dakar, Senegal; and Bobo Dioulasso, Burkina Faso). We recruited patients from the long-term, post-trial cohort of the ANRS 12169/2LADY study that compared the efficacy of three second-line combinations based on boosted protease inhibitors. Participants for our study were HIV-1 infected with multiple mutations including M184V, at first-line failure, aged 18 years and older, on boosted protease inhibitor plus two nucleoside reverse transcriptase inhibitors (NRTI) for at least 48 weeks with at least 48 weeks follow-up in the 2LADY trial, with two viral load measurements of less than 200 copies per mL in the previous 6 months, CD4 counts of more than 100 cells per μL, adherence of at least 90%, and no change to ART in the past 3 months. We randomly assigned participants (1:1) to receive either monotherapy with their boosted protease inhibitor (once-daily darunavir 800 mg [two 400 mg tablets] boosted with ritonavir 100 mg [one tablet] or coformulation of lopinavir 200 mg with ritonavir 50 mg [two tablets taken twice per day]) or to boosted protease inhibitor plus once-daily lamivudine 300 mg (one 300 mg tablet or two 150 mg tablets). Computer-generated randomisation was stratified by study site and viral load at screening (< 50 copies per mL, and 50–200 copies per mL), and concealed from study personnel throughout the inclusion period. After randomisation, treatment allocation was not masked from clinicians or patients]. Patients had follow-up visits at weeks 4 and 12, and every 3 months until 96 weeks; if viral load exceeded 500 copies per mL at any visit, NRTI (tenofovir and lamivudine) were reintroduced into treatment. The primary outcome was the proportion of participants who had treatment failure at 96 weeks in the intention-to-treat analysis, where treatment failure was defined as one of the following: a confirmed viral load of more than 500 copies per mL, reintroduction of NRTI, or interruption of boosted protease inhibitor. We designed the study to detect a difference of 12% between groups in the primary outcome, with an expected 20% of patients having treatment failure in the monotherapy group. This study is registered withClinicalTrials.gov, numberNCT01905059 . Findings: Between March 5, 2014, and Jan 26, 2015, 265 participants were assigned to receive monotherapy (133) or boosted protease inhibitor plus lamivudine (132). At week 48, an independent data safety monitoring board reviewed data, and advised discontinuation of the monotherapy group because the number of failures had exceeded the expected 20%; therefore results here are for week 48. At this point, treatment failure occurred in four (3·0%; 95% CI 0·8–7·6) of 132 participants on dual therapy and 33 (24·8%; 17·7–33·0) of 133 participants on monotherapy (relative risk 8·2, 95% CI 3·0–22·5; odds ratio 10·6, 95% CI 3·6–42·1). The difference between groups (21·8%, 95% CI 13·9–29·7; p<0·0001) showed superiority of dual therapy compared with monotherapy. We recorded 46 severe adverse events of grade 3 or 4 (29 in the monotherapy group, 17 in the boosted protease inhibitor plus lamivudine group); one event in the montherapy group (intoxication resulting from co-administration of ritonavir-boosted lopinavir with an ergotamine derivate) was deemed related to study drug. Two participants in the monotherapy group and one in the dual therapy group died, all from causes not related to study drugs or procedures (one from complications from gastric cancer surgery, one in a work accident, and one from a lung disease of unknown cause). Interpretation: After viral suppression with boosted protease inhibitor plus NRTI in second-line ART, maintenance therapy with boosted protease inhibitor plus lamivudine was associated with a high rate of success, despite the presence of M184V mutations at first-line treatment failure. Results indicated that boosted protease inhibitor monotherapy cannot be recommended for these patients. Funding: Agence National de Recherche sur le Sida et les hépatites and Janssen Pharmaceutica.